UPAYA GURU DALAM MENINGKATKAN PRESTASI BELAJAR PADA MASA PANDEMI COVID-19 - Nur Fadila (Dinamika Sosial: Jurnal Pendidikan Ilmu Pengetahuan Sosial, 2022)
The covid-19 pandemic has caused various problems, especially for the learning system. Learning that is usually done face-to-face in class has turned into online learning. The objectives of this study are: (1) to explain the efforts of teachers in improving social science learning achievement during the Covid-19 pandemic. (2) Explaining the supporting and inhibiting factors of teachers' efforts in improving Social Science learning achievement during the Covid-19 pandemic. This research uses a descriptive qualitative method. The key resource persons in this study were the Social Studies teacher for class VIII, the principal, and students at MTs YPI Al Hidayah. Data collection techniques applied in this study were observation, interviews, and documentation. Data analysis in this study uses data reduction, data presentation, and drawing conclusions. The results of this study reveal that: (1) some of the efforts made by social studies teachers in improving social studies learning achievement during the covid-19 pandemic, namely: doing careful planning, attending educational trainings, using varied teaching methods, choosing learning media that supports, provides motivation to learn, and conducts periodic evaluations; (2) Supporting factors in improving social studies learning achievement during the covid-19 pandemic, namely: giving rewards, peer support, and parental support. As for the inhibiting factors, there are several things, namely: cutting study hours, teacher limitations in controlling online classes, and student delays in taking online classes. Abstrak Pandemi covid-19 telah menimbulkan berbagai masalah khususnya bagi sistem pembelajaran. Pembelajaran yang biasa dilakukan melalui tatap muka di kelas, berubah menjadi pembelajaran dalam jaringan (daring). Tujuan penelitian ini yaitu: (1) menjelaskan upaya guru dalam meningkatkan prestasi belajar Ilmu Pengetahuan Sosial pada masa pandemi Covid-19. (2) Menjelaskan faktor-faktor pendukung dan penghambat upaya guru dalam meningkatkan prestasi belajar Ilmu Pengetahuan Sosial pada masa pandemi Covid-19. Penelitian ini menggunakan metode kualitatif deskriptif. Narasumber kunci dalam penelitian ini adalah guru IPS kelas VIII, kepala sekolah, serta peserta didik di MTs YPI Al Hidayah. Teknik pengumpulan data yang diaplikasikan dalam penelitian ini yakni observasi, wawancara, serta dokumentasi. Analisis data dalam penelitian ini menggunakan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini mengungkapkan bahwa: (1) beberapa upaya yang dilakukan oleh guru IPS dalam meningkatkan prestasi belajar IPS pada masa pandemi covid-19, yaitu: melakukan perencanaan yang matang, mengikuti pelatihan-pelatihan kependidikan, menggunakan metode mengajar yang bervariasi, memilih media pembelajaran yang mendukung, memberikan motivasi belajar, dan melakukan evaluasi secara berkala; (2) Faktor-faktor pendukung dalam meningkatkan prestasi belajar IPS pada masa pandemi covid-19, yaitu: pemberian reward, dukungan teman sebaya, dan dukungan orang tua. Sedangkan untuk faktor penghambatnya terdapat beberapa hal, yaitu: pemotongan jam belajar, keterbatasan guru mengontrol kelas daring, dan keterlambatan siswa mengikuti kelas daring.